Enantioselective Se lattices for stable chiroptoelectronic processing media - Junyoung Kwon; Jae Bum Jeon; Min Gu Lee; Serin Jeong; Won Jin Choi; Kyung Min Kim; Jihyeon Yeom (Nature Communications)
Abstract Chiroptoelectronic devices are crucial for applications in quantum computing, spin optical communications, and magnetic recording. However, the limited efficiency and low stability of conventional circularly polarized light (CPL)-sensing materials have restricted their broader use. Here, we introduce atomic chiral Se nanorod (NRs) films as broadband CPL detectors, leveraging the intrinsic chirality and stability of Se nanocrystals. We also perform incident circular polarization (ICP)-Raman optical activity (ROA) to explore the chiroptical activity of the large-area films. The Se NRs thin films detected CPL across a broad range from ultraviolet (UV) to short-wavelength infrared (SWIR), with a responsivity dissymmetry factor of up to 0.4, maintaining high stability under ambient conditions for longer than 13 months. CPL-sensitive Se NRs with intrinsic chirality have potential applications in chiral photonic synapses, chiral spin devices, and CPL-sensitive photocatalysts. ICP-ROA mapping also advances the analysis of 2D chiral materials.